Comment on Majoron emitting neutrinoless double beta decay in the electroweak chiral gauge extensions - Montero, J. C. [UNESP]; Pires, C. A. de S. [UNESP]; Pleitez, V. [UNESP] (American Physical Society (APS), 1999)
We point out that if the Majoron-like scheme is implemented within a 3-3-1 model, there must exist at least three different mass scales for the scalar vacuum expectation values in the model. ©1999 The American Physical Society.